2000
DOI: 10.1046/j.1439-0272.2000.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorinated hydrocarbons on sperm function in vitro

Abstract: For the past few years there has been controversial discussion of whether environmental pollutants in general, and chlorinated hydrocarbons in particular, may impair male fertility. Organochlorine compounds, e.g. dichlorodiphenyltrichlorothane (DDT) and metabolites, polychlorinated biphenyls (PCBs), dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) are highly persistent in the environment and there is therefore some concern about human exposure. These chlorinated compounds are universally found in human body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Results obtained from the present study indicated that acephate impairs sperm motility, sperm viability, membrane integrity, and sperm capacitation and induced DNA damage in vitro. Similar results were obtained with chlorinated hydrocarbon [19], organophosphates [20, 21], and benzene metabolites [22]. …”
Section: Discussionsupporting
confidence: 84%
“…Results obtained from the present study indicated that acephate impairs sperm motility, sperm viability, membrane integrity, and sperm capacitation and induced DNA damage in vitro. Similar results were obtained with chlorinated hydrocarbon [19], organophosphates [20, 21], and benzene metabolites [22]. …”
Section: Discussionsupporting
confidence: 84%
“…An adverse effect of DDT on male rat fertility was hypothesized [19]. Pflieger-Bruss and Schill reviewed the literature and noted that it might be unlikely that pesticides in vivo could affect sperm function, since in vivo concentrations are far lower than those used in in vitro experiments [20]. This was confirmed by a study having examined semen of 156 patients of an infertility unit in Germany.…”
Section: Discussionmentioning
confidence: 97%
“…Particularly, PCBs have been reported to decrease implantation rate and litter size in mice and rats (Lindner et al 1974) and to cause reproductive failure in mink (Platonow & Karstad 1973). Several reports described the presence of various environmental pollutants, including PCBs, in human follicular fluid (Trapp et al 1984, Pflieger-Bruss & Schill 2000 and human ovarian tissue (Mes 1990).…”
Section: Introductionmentioning
confidence: 99%